Variant insertion of coracobrachialis muscle-morphological significance, embryological basis and clinical importance - Guha, R; Satyanarayana, N; Reddy, CK; Jayasri, N; Nitin, V; Praveen, G; Sunitha, P; Datta, AK (Journal of College of Medical Sciences-Nepal, 2010)
The coracobrachialis muscle in the arm is morphologically the sole representative of adductor group muscle in the arm, but such function during the process of evolution became insignificant in man. It is more important morphologically than functionally. Variant insertion of the coracobrachialis muscle was found during routine dissection of an adult male cadaver in the Department of Anatomy, College of Medical Sciences, and Bharatpur, Nepal. Normally the coracobrachialis muscle is inserted into the middle of the medial border of the humerus. In the present case an additional slender tendon passed inferiorly, crossing anterior to the median nerve and brachial artery, before attaching to the medial epicondyle of the humerus. Most of the proximal part of the tendon gave rise to an aponeurotic expansion that inserted into the distal medial border of the humerus. The tendinous insertion and aponeurotic expansion may represent a variant of the coracobrachialis longus (Wood's) muscle and the internal brachial ligament or the ligament of Struthers. The ulnar nerve was found to be traversing below the aponeurotic expansion. This type of anomalous insertion of coracobrachialis muscle may lead to compression of median nerve, brachial artery and ulnar nerve. Key words: Coracobrachialis muscle; ligament of Struthers; median nerve; brachial artery; ulnar nerve. DOI: 10.3126/jcmsn.v6i2.3616 Journal of college of Medical Sciences-Nepal, 2010, Vol.6, No-2, 42-46